Responsibility and science communication: scientists' experiences of and perspectives on public communication activities. Issue 2 (4th May 2018) - Loroño-Leturiondo, Maria; Davies, Sarah R.
ABSTRACT: Public communication of science and technology is central to ideas about responsible research and innovation (RRI). This paper presents findings from a focus group study, carried out with natural scientists based in the Basque Country, which explored researchers' ideas about public communication. We identify three key themes from this data: these scientists framed successful science communication as producing emotionally 'good experiences' for audiences; they depicted such communication as a responsibility that they had to society and that was thus carried out for the good of the public; and they described themselves as responsible for the success of science communication. Scientists thus emphasised their own responsibility for ensuring a successful science communication process. In closing we reflect on what these findings mean for the promotion and practice of RRI, suggesting that a greater focus should be placed on the character of responsibility as well as its presence.